Impasses do desacolhimento institucional por maioridade: psicanálise e articulação de rede territorial - Ferreira, Mariana Belluzzi (2017)
This dissertation’s main objective is to focus on the silencing often perpetuated by the actors of the territorial services network regarding the process of unsheltering as teenagers reach the age of majority. We intend to concentrate, as well, on the discourses that individualize the adolescent's exposure to the repetition of unprotected and violence situations during this process; these situations arise from the lack of a place defined in the social assistance policy to the deinstitutionalization of the adolescent. Conceiving the process of unsheltering when teenagers reach full legal age as a process of deinstitutionalization, we conducted a research-intervention with professionals of the inter-sectorial network of a territory of the city of São Paulo. A group of Conversation in Psychoanalysis has been formed with these professionals. The main objectives of this group was to realized a case study and the construction of working strategies with the subject and their network of relationships. Under contributions from the Psychoanalysis, Institutional Analysis and Social Assistance Policy and from the group’s discussions, we sought to discuss the family and adolescence institutions, central to the process of unsheltering by entering full legal age, as well as their current conceptions in the social service policy. The family was discussed as a social-historical construction, its central place in social service policy, as well as the effects of a familiarization of social assistance policy, particularly in this process of unsheltering, that conceives the family as a natural and exclusive place of care and protection. Such mode of reasoning hinders the construction of other stances of recognition and belonging for the adolescent in the process of becoming a non-citizen due to the end of protection for reaching full legal age. We then sought to discuss the concept of adolescence that prevails in social assistance policy, based on the developmental approach present in the legal speech. Conceived in a universal and a-historical way, this conception comprises the subjective constitution as dissociated from the social bond, making it difficult to recognize the social and political conflicts present in the institutional and social scenes, imputing them to the adolescent through pathological and criminalizing speeches. Trying to deny the naturalization of the notion of adolescence, we present a conception that is articulated with the subject's enrollment in the social bond, conceiving it as a social-political construction. Family, institutional and social speeches offer adolescents a place of recognition and belonging to the social scene. We understand that adolescents, in the process of unsheltering by reaching the age of majority, in the face of the obliteration of family speech and the attribution of a social speech laden with stigmas, are left to their own speech. We also note the absence of an inter-sectoral network as a symptomatic signal of the process of making adolescents unprotected by reaching the age of majority, as well as the possibility of carrying out a social network job. This work allowed the construction of specific intervention devices for this process of unsheltering, and above all it permitted building up a social assistance speech that sought to include them in this policy